2021
DOI: 10.5334/joc.145
|View full text |Cite
|
Sign up to set email alerts
|

Time-Based Transition Expectancy in Task Switching: Do We Need to Know the Task to Switch to?

Abstract: Recent research has shown that humans are able to implicitly adapt to time-transition contingencies in a task-switching paradigm, indicated by better performance in trials where the task transition (switch vs. repetition) is validly predicted by the pre-target interval compared to trials with invalidly predicted transitions. As participants switched between only two different tasks, not only the transition, but also the specific task was predictable; at least indirectly when taking into account the temporally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Since cognitive processes involved in task switch and task repetition trials differ (see Introduction), an expectancy for switch-related processes should have influenced task switching and task repetition differently. In line with most previous time-based expectancy studies which apply task switching scenarios (Aufschnaiter et al, 2018a, 2018b2020;2021), such an effect could not be detected in our study. However, this interpretation conflicts with a study by Wendt and Kiesel (2012), which demonstrated a benefit from time-based expectancy for conflict adaptation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Since cognitive processes involved in task switch and task repetition trials differ (see Introduction), an expectancy for switch-related processes should have influenced task switching and task repetition differently. In line with most previous time-based expectancy studies which apply task switching scenarios (Aufschnaiter et al, 2018a, 2018b2020;2021), such an effect could not be detected in our study. However, this interpretation conflicts with a study by Wendt and Kiesel (2012), which demonstrated a benefit from time-based expectancy for conflict adaptation.…”
Section: Discussionsupporting
confidence: 81%
“…task repetition compared to task switches). Such an interaction was only observed in Experiment 1 in the study of Aufschnaiter et al (2018b), whereas in most experiments task transition did not interact with time-based expectancy (see Aufschnaiter et al, 2018a, 2018b2020;2021). We still included the factor transition as well the additional factor foreperiod for each of the analyses in order to elaborate potential interactions.…”
Section: Time-based Expectancymentioning
confidence: 99%
“…Time expectancy is usually investigated by employing the variable foreperiod (FP) paradigm, in which the time span, called the FP, between the onset of the warning signal and the presentation of the target stimulus differs between trials within one experimental block (Los et al, 2001 ; Schröter et al, 2015 ; Steinborn et al, 2009 ). As time expectancy and time-based expectancy usually do not interact, time expectancy will not be further discussed in the present study (see Aufschnaiter et al, 2018a ; Aufschnaiter et al, 2021 ; Kunchulia & Thomaschke, 2016 ).…”
mentioning
confidence: 84%
“…Footnote 1 (continued) (see Aufschnaiter et al, 2018a;Aufschnaiter et al, 2021;Kunchulia & Thomaschke, 2016). 2 For the sake of consistency, we will use the term "foreperiod" instead of "time interval" from here on throughout the text.…”
Section: Investigating Time-based Expectancy Beyond Binary Timing Scenarios: Evidence From a Paradigm Employing Three Predictive Pre-targmentioning
confidence: 99%
“…They argue that the complexity of the visual background leads to an attenuation of n-2 task repetition costs. Aufschnaiter et al (2021) demonstrate that task switches and repetitions can be prepared if they become predictable by the duration of pre-target intervals. The authors propose a two-stage preparation model according to which task switches and repetitions are prepared in an unspecific manner, such as by previous task set inhibition, based on expectancies derived from the duration of intertask transitions.…”
mentioning
confidence: 86%